STRATEGIES TO INCREASE THE COMPETITIVENESS OF INDONESIAN MSMES IN THE GLOBAL MARKET THROUGH HALAL PRODUCT DEVELOPMENT - Ichsan, Reza Nurul (Strategic Management Business Journal, 2024)
Research background: Strategies to Improve the Competitiveness of Indonesian MSMEs in the Global Halal Market in overcoming the challenges faced by Indonesian MSMEs in the halal industry requires a multi-pronged approach, by implementing these strategies, Indonesian MSMEs can enhance their competitiveness in the global halal market and contribute to the growth of the country's economy. Purpose of the article: The formulation of the problem of this research is what are the Strategies For Improving The Savings Of Indonesia's Msmes In The Global Markets Through The Development Of Halalal Products. Methods: This research employs a qualitative approach, utilizing a comprehensive literature review to investigate the strategies for enhancing the competitiveness of Indonesian MSMEs in the global market through the development of halal products. JEL Classification: M10, M13